Kesadaran Diri Proses Pembentukan Karakter Islam - Malikah, Malikah (Al-Ulum, 2013)
This paper elaborates about self-awareness that is a process of forming the Islam character. In the self-awareness, human is faced on opposite side; that is, they are to know the power of strength and the weakness of ourselves. Both of them there is synergy, when the man can use them optimally and proportionally, the success of his/her can be gained. To grow the self-awareness is needed character forming which is started from the values is found from many kind of resources, then the values form thought pattern of someone totally and bear as vision. The vision turn into the mind area and form mind nuance, then totally come out as mentality, flow through physic area and bear action as attitude form.